On whom would I want to depend; Humans or nature? - Mike Farjam (Friedrich Schiller University Jena, 2015)
We study in an experiment whether humans prefer to depend on decisions of other humans (social uncertainty) or states of nature (environmental uncertainty). In the social uncertainty treatments subjects depend only on past decisions of other humans. This is the first experiment that studies social uncertainty that does not derive from a strategic situation. The results indicate that even without any strategic context humans prefer lotteries where the distribution of outcomes is due to states of nature to lotteries where the distribution is due to decisions of humans. This holds even when distributions are identical and known to subjects.
Keywords: C91; D81; 330; ambiguity aversion; experiment; risk; social uncertainty